The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.37501/soilsa/123322
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus transport as a criterion for soil categorisation

Abstract: Water pollution, both surface and underground, by agricultural activity is a relatively serious problem. The pollutants are transported from the soil to the water. The aim of this paper is to evaluate the soil transport function on the basis of present knowledge of soil nutrient (nitrogen and phosphorus) transport and soil and local properties. The west Slovak lowlands, south Slovak basins and east Slovak highlands were selected due to their different climate and soil parameters. Soil nutrient transport was cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Due to the non-renewable resources as the demand for such a valuable raw material as precious metals grows, poor deposits will soon be exploited. Due to the very low content of the components to be obtained, the technology is demanding and it is also associated with environmental risks (Jeleň et al 2007;Hronček 2008;Hronček et al 2018;Reiffers et al 2018;Torma et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the non-renewable resources as the demand for such a valuable raw material as precious metals grows, poor deposits will soon be exploited. Due to the very low content of the components to be obtained, the technology is demanding and it is also associated with environmental risks (Jeleň et al 2007;Hronček 2008;Hronček et al 2018;Reiffers et al 2018;Torma et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The relationships described above apply analogously to nitrogen compounds. This is because waters on agricultural land are characterized by high concentrations of nutrients (including NO 2 − -N, NO 3 − -N, and NH 4 + -N) whose sources are organic and mineral fertilizers [42,43]. Among the measured forms of nitrogen in the waters at the research sites, elevated concentrations of NO 2 − -N were observed.…”
Section: Indicators Characterizing Biogenic Conditionsmentioning
confidence: 91%
“…Following the accumulation of phosphorus and the saturation of binding sites on soil particles, the ability of soil to retain phosphorus decreases and the possibility of phosphorus losses through runoff or drainage water increases, which can lead to eutrophication of aquatic environments (e.g. Sims et al, 1998;Smith et al, 1999;Allen et al, 2006;Torma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%